Wpływ regionalnych odmian języka na współczesną polszczyznę potoczną - Kucharzyk, Renata (Papers in Linguistics, 2019)
The subject of the article is the presence of regional features in the colloquial Polish. One may notice that contemporary Polish is not homogeneous, some regional or dialectal properties are present in the widely understood colloquial communication. The issue was discussed on the basis of the material excerpted from the Internet forums. The author presents selected features within the area of phonetics and lexis that were found in the Internet users’ posted messages.